2015
DOI: 10.1063/1.4921083
|View full text |Cite
|
Sign up to set email alerts
|

Strain-controlled optical absorption in epitaxial ferroelectric BaTiO3 films

Abstract: A lattice strain of 0.3%–1.3% is achieved in epitaxial tetragonal BaTiO3 films grown on (001)-oriented SrTiO3 single-crystal substrates. Our experimental studies of absorption spectra in the range of 0.74–9.0 eV demonstrate that epitaxy produces significant changes in the optical properties of the films compared with those of a reference polydomain BaTiO3 crystal: the absorption edge and the peak at 5 eV strongly blue-shift by 0.2–0.4 eV, the magnitude of the peak at 5 eV drops, and certain spectral features d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The dielectric functions and optical constants of the films were extracted from the ellipsometric spectra using a commercial WVASE32 software package. More details for the ellipsometric procedures can be found elsewhere [23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…The dielectric functions and optical constants of the films were extracted from the ellipsometric spectra using a commercial WVASE32 software package. More details for the ellipsometric procedures can be found elsewhere [23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…The BTO film was grown on top of the STO single-crystalline substrate by pulsed laser deposition (Chernova et al, 2015). Because of the mismatch between the lattice parameters of BTO and STO, the theoretical biaxial in-plane (parallel to the substrate surface) misfit strain is $2.5% compressive in BTO at the deposition temperature of 973 K. The misfit strain is known to relax with increasing film thickness and it may be completely relaxed in BTO at the growth temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to that, this compressive strain found in treated BaTiO 3 may lead to reduce the symmetry of the crystal structure. The reduction in symmetry probably enhanced the piezoelectric properties in treated BaTiO 3 as compared to control [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that distortion in perovskite BatiO 3 reduced symmetry, which enhanced its magnetic and electrical properties [7]. Moreover, Chernova et al demonstrated that strain induced in BaTiO 3 unit cell enhanced its ferroelectric polarizations [8]. Thus, after considering the vast importance of BatiO 3 and its crystal structure in several applications, authors wish to investigate an approach that could be beneficial to modify the atomic Impact of Biofield Treatment on Atomic and Structural Characteristics of Barium Titanate Powder and structural properties of BatiO 3 powder.…”
Section: Introductionmentioning
confidence: 99%